Ischemic stroke as a rare cause of seizures in a newborn - case report - Karolina Widłak; Agnieszka Wójtowicz; Robert Ściślak; Justyna Drankowska; Michał Kos; Aleksandra Szuster; Agata Tarkowska; Elżbieta Szponar; Wanda Furmaga-Jabłońska (Kazimierz Wielki University, 2019)
Background: Identifying etiology of seizures is the primary clinical objective in the management of neonatal seizures (NS). About 85 % of NS cases occurr as a consequence of a specific, identifiable etiology. Causes of symptomatic NS can be broadly categorized as: hypoxic-ischemic encephalopathy, electrolyte or metabolic disturbances, CNS or systemic infections, developmental defects and acquired structural brain lesions, including hemorrhagic or ischemic stroke. Ischemic stroke is characterized as a sudden focal or generalized brain function disruption, whose symptoms tend to last longer than 24 hours (or cause death) and have no other reason but a vascular one. The reported annual incidence is estimated at one per 4000 live births for neonates. The aim of this case report is to present diagnostic difficulties in case of ischemic stroke in apparently healthy neonate. This case concerns a patient - a full-term male newborn, who was in a good condition in the first 3 days after birth. At the beginning of the 4th day of life 3 episodes of right-sided clonic seizures with right-sided nystagmus occurred and which was the reason for admitting the patient to the Department of Neonate and Infant Pathology. Shortly after arrival the seizures appeared again. Laboratory tests showed slightly lowered glucose level and elevated serum concentration of lactic acid. The ultrasound examination of the head revealed a small right-sided subependymal cyst. The patient's condition was deteriorating, with recurring righ-sided clonic and tonic seizures accompanied by apnea and desaturation that required resuscitation efforts. Because of worsening state of the patient, CT scan was performed. The CT examination revealed a hypodensic area in the left parietal region and cerebral edema, which indicated a possible ischemic stroke. Conclusions: The absence of visible pathologies in the ultrasound examination of the head does not necessarily indicate a lack of CSN abnormalities. More precise imaging tests are needed to identify the cause of NS.